Endometritis in Cattle: A Review of Current Understanding and Practical Causes of Repeat Breeding - Hermadi, Herry Agoes; Khairullah, Aswin Rafif; Damayanti, Yenny; Safitri, Erma; Tyasningsih, Wiwiek; Warsito, Sunaryo Hadi; Kusala, Muhammad Khaliim Jati; Wibowo, Syahputra; Moses, Ikechukwu Benjamin; Kurniawan, Moh. Adiba; Wardhani, Bantari Wisynu Kusuma; Prasetyo, Saputro Teguh; et al. (Trends in Sciences, 2025)
One of the most prevalent reproductive illnesses that significantly reduce the livestock industry's profitability is endometritis. Endometritis is an inflammation that occurs in the uterine mucosa (endometrium), which is the inner layer of the uterine wall. Trueperella pyogenes is the most common organism linked to endometritis in cattle. Endometritis is a reproductive condition characterized by signs of repeated breeding. It is evident that there is a correlation between the season of delivery and the occurrence of endometritis, with a higher frequency of endometritis occurring during autumnal deliveries. Although endometritis primarily affects cattle, it can also affect sheep, goats, pigs, horses, and camels. The primary clinical signs of endometritis include an enlarged uterus and an expanded cervical diameter, as well as purulent vaginal discharge. Endometritis is frequently diagnosed using the traditional method based on clinical signs and rectal examination. Cattle can contract endometritis from a variety of sources, including retained fetal membranes, assisted birthing procedures, contamination from dead calves, microbes entering the uterus during delivery, and immunological dysfunction in the genital tract of cows that have recently suffered from dystocia. The standard treatment for endometritis consists of a mix of hormones, such as uterotonics, Nonsteroidal Anti-inflammatory Drugs (NSAIDs), and antibiotics. Important strategies to lower endometritis include the following management practices: Prevention of postpartum metabolic disorders, early detection and treatment of postpartum uterine diseases, and close monitoring and support during delivery. HIGHLIGHTS This article provides a comprehensive review of endometritis disease in cattle. Endometritis in cattle is an inflammation of the inner lining of the uterus (endometrium), often due to bacterial infection after calving. Endometritis can cause decreased reproductive efficiency and economic losses for the farm. GRAPHICAL ABSTRACT